"The quietness of the place calmed my troubled mind": The restorative potential of environments in an existential rehabilitation programme for patients with cancer*. (February 2021) - Roessler, K. K.; Graven, V.; la Cour, K.; Hvidt, N. C.; Rottmann, N.; Hvidt, E. Assing
In the following article, the restorative potential of the environment in a cancer rehabilitation programme is analysed and discussed. The programme was developed as a transdisciplinary cooperation of psychologists, theologians, philosophers, and artists. To investigate the importance of environments, six qualitative focus group interviews were performed with 36 Danish cancer patients (30 females; six males) who attended the programme either at The Danish Knowledge Centre for Rehabilitation and Palliative Care (REHPA), a former hospital building adapted for rehabilitation, or at Løgumkloster Refugium, an old monastery, used as a place for retreat. The data were analysed using a content analysis that took a psychodynamic and hermeneutic approach as its point of departure. Outcomes associated with the environment that enhanced the well-being of the patients were feelings: a) of being close to nature, b) of being protected, c) of the spirit of place, and d) of experiencing narratives of peace. Our programme supports the idea, that environments in which cancer rehabilitation takes place can trigger different emotions and fulfil different existential needs. Aesthetic, historical, and spiritual aspects of an environment can help individuals to respond to existential challenges and can induce hope. Our study contributes knowledge about the interplay between existential well-being and aspects of the environment.